If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 2j = -1j Solving 12 + 2j = -1j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add 'j' to each side of the equation. 12 + 2j + j = -1j + j Combine like terms: 2j + j = 3j 12 + 3j = -1j + j Combine like terms: -1j + j = 0 12 + 3j = 0 Add '-12' to each side of the equation. 12 + -12 + 3j = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 3j = 0 + -12 3j = 0 + -12 Combine like terms: 0 + -12 = -12 3j = -12 Divide each side by '3'. j = -4 Simplifying j = -4
| 5X=245 | | Y=-4x^2+16x-16 | | (4x+25)+x=180 | | 20+2k=-18k | | 5x+6=30+3x | | 5p^2+3=12p | | 3x^2+9x=-30 | | 5x/3+15/2=2x+10 | | -3(c+3)=4(c+3) | | 11-k=-10 | | 2(c-14)=-8 | | (4x+25)+y=180 | | x/2+1,5=6 | | y=5t+30 | | 808-m=722 | | 3(a+0.35)=1.5 | | -6n-4=2n+4(1-3n) | | -49=635-j | | 0=-16t^2+40t+6 | | 25+4x=180 | | m^8-n^8=0 | | 714=17(k-935) | | 8+3t=13-t | | 3/w-8 | | 6x^3-37x^2+67x-30=0 | | 2(3t-4)=5(2t-4) | | -x-15=8(-2x-2)+1 | | 24=2(p+73)-2 | | 13y+-1.8=-5y+3.6 | | 2x+13,8=35,7 | | 2x-5+2-x= | | 1/3(x-7=1 |